Maquila Workers' Health: Basic Issues, What is Known, and a Pilot Study in Nicaragua - Lylliam Perpetuo López; Luis Blanco R.; Aurora Aragón B.; Timo Partanen (Social Medicine Publication Group, 2024)
Occupational health issues identified in maquilas include respiratory, musculoskeletal, psychological problems, and accidents. This study identifies the basic health issues, as well as the sources and investigational methods needed for drafting health standards for maquilas. It sets out conceptual guidelines, suggesting general methodological strategies appropriate for studies of workers' health and its determinants in the maquiladora sector. The conceptual-methodological model is based on 1) a review of relevant studies, 2) a mixed methods pilot feasibility study within the community of workers and social actors of a textile maquila in Nicaragua, and 3) the conceptual-methodological integration of a literature review with the results of the pilot study. The main issues identified are the organization of work, health, governmental regulation, family and gender, infrastructure and environment. Methodological recommendations focus on the principle of triangulation; the use of anonymous questionnaires and focus groups to examine specific issues; individual interviews with management personnel and members of the community; and the value of family members as key informers on the impact on family, environment and community. Observation of actual work procedures is ideal but not always possible. A joint health and safety committee and a health services unit would be key instruments in the prevention of accidents and illness and in health promotion and care.